حماية حق تربية الأبناء الأسرية في القانون الدولي والتشريع الجزائري - شيباني, عبد الله; خلف, بوبكر (University of Eloued جامعة الوادي, 2022)
يعتبر الأبناء من أَوْلى فئات المجتمع بالرعاية والاهتمام، فهم كنوز أُسرهم والثروة الحقيقية لبلدهم إنْ أُحسنت تربيتهم والعناية بهم. لذا يُعتبر من الأهمية بمكان القيام بواجب التربية اتجاه الأبناء، وضرورة القيام بهذا الواجب في الأسرة من الآباء ومن لهم عليهم ولاية؛ فالرعاية والتربية التي يتلقّاها الطفل من أبويْه أو من ينوبهم، هي بمثابة حجر الأساس في بنائه النفسي والاجتماعي، فإذا كان بناء الأسرة قوي وسليم في تنشئة الطفل فإنّه يكون سليم السلوك قويم الأخلاق. الأمر الذي يستوجب على المشرع الوطني الاهتمام بالتشريع القانوني الذي يكون له الدور الأساس في حماية حق تربية الأبناء في مجال الأسرة، من خلال سنّه القواعد القانونية التي تُبرز أهمّية الأسرة في تربية الأبناء ومسؤولية الآباء عن تنشئتهم، مع توضيح الآليات ودورها في التكفل بحماية حقهم في التربية، وكذا الجزاءات العقابية الواجب تسليطها على آبائهم أو أوليائهمعند التقصير في أداء هذا الحق أو الاعتداء عليه. Children are considered among the first groups of society who need care and attention. They are the treasures of their families and the real wealth of their country if they arewellraised and cared. Therefore, it is considered of great importance to carry out the duty to bring childrenup, and the necessity of carrying it out in the family by their parents and those who have jurisdiction over them; Care and rearing that the child receives from his parents or their representatives are the cornerstone of his psychosocial construction. This requires the national legislator to pay attention to legal legislation that has the primary role in protecting the right to raise children in the family, by enacting legal rules that highlight the importance of the family in raising children and the parents' responsibility for their upbringing and clarifying the mechanisms andits roleto ensure the protection of their right to raising. As well as the penal sanctions that must be imposed on their parents or guardians when they fail to fulfill this right or violate it.
Protection of the right to raise family children in international law and Algerian legislation
مقال
Keywords: حق التربية؛ الأبناء؛ الأسرة؛ آليات التكفل بحق تربية الأبناء؛ الحماية الجزائية لتربية الأبناء; the right to raising; children; family; Mechanisms to guarantee the right to raise children; Penal protection for raising children